P.106: Magnetic Resonant Wireless Power Transmission to Thin OLED Lighting Panel. Issue 1 (1st July 2013) - Kim, Yong‐Hae; Han, Jun‐Han; Lee, Myung‐Lae; Cheon, Sanghoon; Kang, Seung‐Youl; Ryu, Hojun; Zyung, Taehyoung; Lee, Jeong‐Ik; Chu, Hye Yong
Abstract We used the magnetic resonant wireless power transmission technology to lit thin OLED lighting panels. For the magnetic resonant wireless power transmission, we used small and thin four layer printed circuit board for the receiver. The resonant frequency is lowered up to 457 kHz for the electromagnetic regulation.